A Handbook for Supporting Today's Graduate Students - Nguyen, David J. (Stylus Publishing, LLC, 2022)
"Written for graduate school administrators, student affairs professionals, and faculty, this book offers ways to better support todays graduate student population, addresses the needs of todays changing student demography and considers the challenges todays graduate students face inside and outside of the classroom"